2019
DOI: 10.1111/jam.14532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of altered environmental conditions as a decontamination approach for nonspore‐forming biological agents

Abstract: Aims The purpose of this study was to evaluate the effects of altered environmental conditions on the persistence of Francisella tularensis bacteria and Venezuelan equine encephalitis virus (VEEV), on two material types. Methods and Results Francisella tularensis (F.t.) and VEEV were inoculated (c. 1 × 108 colony‐forming units or PFU), dried onto porous and nonporous fomites (glass and paper), and exposed to combinations of altered environmental conditions ranging from 22 to 60°C and 30 to 75% relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…This study has also confirmed that storage under warm conditions will increase the rate of natural attenuation and reduce the time required to achieve LOQ by 0-3 days based on material type, and conversely, under cold storage conditions, the attenuation rate steeply declines. These findings are consistent with similar research efforts where the ability to achieve 6 LR or greater for Venezuelan Equine Encephalitic virus on both porous and non-porous materials was achieved in 6-12 h as compared to control samples held at ambient temperatures showing minimal LR after 96 h. (Richter et al, 2019). More recently, the half-life of SARS-CoV-2 virus on non-porous fomites stored at 24°C ranged from 6.3 to 18.6 h; however, by increasing the temperature to 35°C, the half-life was reduced to 1.0 to 8.9 (Biryukov et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study has also confirmed that storage under warm conditions will increase the rate of natural attenuation and reduce the time required to achieve LOQ by 0-3 days based on material type, and conversely, under cold storage conditions, the attenuation rate steeply declines. These findings are consistent with similar research efforts where the ability to achieve 6 LR or greater for Venezuelan Equine Encephalitic virus on both porous and non-porous materials was achieved in 6-12 h as compared to control samples held at ambient temperatures showing minimal LR after 96 h. (Richter et al, 2019). More recently, the half-life of SARS-CoV-2 virus on non-porous fomites stored at 24°C ranged from 6.3 to 18.6 h; however, by increasing the temperature to 35°C, the half-life was reduced to 1.0 to 8.9 (Biryukov et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…While statistical analysis was not conducted, the survival of SARS-CoV-2 virus and the porosity of the material type did not result in any obvious paired effect that has been previously observed for other similar environmental persistence evaluations (e.g. porous materials result in slower reduction in viability while non-porous materials result in faster reduction; Richter et al, 2019). cover) were evaluated at ambient temperature conditions in a stacked configuration, to reflect routine storage conditions of the materials common in library facilities.…”
Section: Ambient Temperaturementioning
confidence: 65%
See 1 more Smart Citation
“…The longest survival was seen at 38 ± 2 °C and 41 ± 5% relative humidity: both strains were still detectable after 10 days on glass. On paper, Schu4 was inactivated after 96 h and LVS after 24 h [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to calculating an LR value for each test condition and time point, we have determined inactivation rates (as D -values) for positive controls and the coupons exposed to HPV. D -values are commonly used to quantify the rate of inactivation of a microbial population, over several time points and are expressed as the time in h to reach 1 LR from the initially recovered PFU amount. , For brevity, these calculated D -values for each phage and test condition, as well as further information on the statistical methods and their detailed results, are found in the Supporting Information (SI). The D -values were calculated as the ratio of the shorter of the number of hours to achieve complete decontamination (i.e., when the phage was not detected) or the end of the decontamination test period; divided by the difference between the log recovery of the phage at the time point and the log recovery at time zero.…”
Section: Methodsmentioning
confidence: 99%